PIEZO1 Ion Channel Mediates Ionizing Radiation-Induced Pulmonary Endothelial Cell Ferroptosis via Ca2+/Calpain/VE-Cadherin Signaling - Guo, Xue-Wei; Zhang, Hao; Huang, Jia-Qi; Wang, Si-Nian; Lu, Yan; Cheng, Bo; Dong, Su-He; Wang, Ying-Ying; Li, Feng-Sheng; Li, Yong-Wang (Frontiers in Molecular Biosciences, 2021)
Pulmonary endothelial cell dysfunction plays an important role in ionizing radiation (IR)-induced lung injury. Whether pulmonary endothelial cell ferroptosis occurs after IR and what are the underlying mechanisms remain elusive. Here, we demonstrate that 15-Gy IR induced ferroptosis characterized by lethal accumulation of reactive oxygen species (ROS), lipid peroxidation, mitochondria shrinkage, and decreased glutathione peroxidase 4 (GPX4) and SLC7A11 expression in pulmonary endothelial cells. The phenomena could be mimicked by Yoda1, a specific activator of mechanosensitive calcium channel PIEZO1. PIEZO1 protein expression was upregulated by IR in vivo and in vitro. The increased PIEZO1 expression after IR was accompanied with increased calcium influx and increased calpain activity. The effects of radiation on lung endothelial cell ferroptosis was partly reversed by inhibition of PIEZO1 activity using the selective inhibitor GsMTx4 or inhibition of downstreaming Ca2+/calpain signaling using PD151746. Both radiation and activation of PIEZO1 led to increased degradation of VE-cadherin, while PD151746 blocked these effects. VE-cadherin knockdown by specific siRNA causes ferroptosis-like phenomena with increased ROS and lipid peroxidation in the lung endothelial cells. Overexpression of VE-cadherin partly recused the ferroptosis caused by IR or PIEZO1 activation as supported by decreased ROS production, lipid peroxidation and mitochondria shrinkage compared to IR or PIEZO1 activation alone. In summary, our study reveals a previously unrecognized role of PIEZO1 in modulating ferroptosis, providing a new target for future mitigation of radiation lung injury.